2014
DOI: 10.3109/10715762.2014.896003
|View full text |Cite
|
Sign up to set email alerts
|

Gender-dimorphic regulation of antioxidant proteins in response to high-fat diet and sex steroid hormones in rats

Abstract: Despite the fact that gender dimorphism in diet-induced oxidative stress is associated with steroid sex hormones, there are some contradictory results concerning roles of steroid hormones in gender dimorphism. To evaluate the role of gender dimorphism as well as the effects of sex steroid hormones in response to high-fat diet (HFD)-induced oxidative stress, we measured cellular levels of major antioxidant proteins in the liver, abdominal white adipose tissue, and skeletal muscles of Sprague-Dawley rats followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…It is well known that the placenta functions and adapts to an adverse intrauterine environment in a sex-specific manner (reviewed by Clifton, 2010). Furthermore, generation of oxidative stress differs in both male and female fetuses and placentae under conditions of adverse prenatal stress (Chaudhari et al., 2014). Our current study further demonstrates a dichotomous sex-specific and nMitoQ-specific effect on the placenta and ultimately fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the placenta functions and adapts to an adverse intrauterine environment in a sex-specific manner (reviewed by Clifton, 2010). Furthermore, generation of oxidative stress differs in both male and female fetuses and placentae under conditions of adverse prenatal stress (Chaudhari et al., 2014). Our current study further demonstrates a dichotomous sex-specific and nMitoQ-specific effect on the placenta and ultimately fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria from female rats generate half the amount of hydrogen produced by males and have higher levels of mitochondrial reduced glutathione (Borras et al 2007). Cellular levels of anti-oxidant proteins, including catalase, glutathione peroxidase, peroxiredoxin, superoxide dismutase and thioredoxin, are regulated in sex-dependent manner in metabolic tissues in ways that may result in females having a greater capacity to combat oxidative stress than males (Chaudhari et al 2014). Further studies will need to be conducted to address these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we found that several metabolic proteins in white adipose tissue (WAT), brown adipose tissue (BAT), the liver, and other metabolic tissues are regulated in a sex-dependent manner [25][26][27]. Thus, we hypothesized that the various expression patterns of those proteins are the result of differential hormonal regulation, specifically estrogen.…”
Section: Introductionmentioning
confidence: 90%